Response of Tomato (Lycopersicon esculentum L.) at Varying Levels of Soil Applied Potassium - Zia-ul-Hassan; K.A. Kubar; M.A. Chhajro; M.N. Kandhro; G.M. Jamro; K.H. Talpur; N. Talpur (Journal of Basic & Applied Sciences, 2016)
The pot study was conducted during autumn 2015 at | department of Soil Science, Sindh Agriculture University, Tandojam Pakistan to assess the effect of soil applied potassium sulphate (K2SO4) fertilizer on growth, biomass production and K accumulation of plants of tomato variety Roma. The study was executed in a net-house under natural conditions following completely randomized design. There were six treatments (0, 50, 100, 150, 200 and 250 kg K2O ha-1), each repeated thrice. A recommended blanket dose of 150 kg nitrogen and 75 kg phosphorus ha-1was also given to the crop. Tomato plants were raised in five kg plastic pots filled with a K-deficient soil (119 mg kg-1). Results of the study indicated that K nutrition significantly enhanced growth, biomass production and K accumulation of tomato plants. K nutrition augmented different plant height (49%), shoot diameter (103%), fresh biomass (134%), dry biomass (182%), number of leaves (75%) and K concentration (3.1 fold). It is concluded that a dose of 100 kg K2O ha-1 was the most optimum for tomato plants at early growth stage. These results need to be verified under field conditions at maturity level of tomatoes.